Application of three-dimensional visualization technology in the anatomical variations of hilar bile ducts in Chinese population - Li, Xiaofeng; Duan, Renpeng; He, Yifeng; Qin, Jiawei; Liu, Ruijian; Dai, Siqin; Zhou, Jiawei; Zeng, Xiancheng; Duan, Juan; Gao, Peng; Yang, Xiaoqiao; Li, Cheng (Frontiers in Surgery, 2022)
The aim of this study was to establish three-dimensional models of the biliary tract of Chinese people using the Hisense computer-aided surgery (CAS) system and to explore the branching patterns and variation types of the biliary system under the study of 3D reconstruction of the biliary tract. Three-dimensional models of the biliary tract were reconstructed in 50 patients using the Hisense CAS system. The branching patterns of intrahepatic bile ducts were observed. The biliary tract was classified according to the confluence of the right posterior sectoral duct (RPSD), right anterior sectoral duct (RASD) and left hepatic duct (LHD), and the presence or absence of accessory hepatic ducts. The 3D models of the bile ducts were successfully reconstructed in 50 Chinese patients. The branching patterns of the bile ducts were classified into 7 types. The anatomy of the bile ducts was typical in 54% of cases (n=27), showed triple confluence in 10% (n=5), crossover anomaly in 14% (n=7), which means anomalous drainage of the RPSD into the LHD, anomalous drainage of the RPSD into the common hepatic duct in 10% (n=5), anomalous drainage of the RPSD into the cystic duct in 2% (n=1), absence of left main hepatic duct in 1% (n=1), presence of accessory duct in 8% (n=4). Among them, there were 3 cases of accessory hepatic ducts coexisting with other variation types. By using the Hisense CAS system to establish 3D models of the biliary tract of the Chinese people, we established the branching model of the second-order bile ducts, which has important value for the classification of the biliary system and its variation types.